Rethinking Religious Moderation: Revitalisasi Konsep Manusia Perspektif Filsafat Pendidikan Islam dalam Konteks Multikultural - Nasri, Ulyan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
The increasingly complex multicultural context presents various social, political, and religious challenges worldwide. This research aims to reconsider the concept of religious moderation through the lens of Islamic philosophy of education, with a focus on revitalizing the understanding of humanity in a multicultural context. The study employs a qualitative approach by analyzing relevant theoretical literature, including the works of Islamic scholars and philosophy of education. Through this analysis, the research seeks to identify key elements in the concept of humanity in Islam that can support religious moderation in a multicultural context. The findings of this research underscore the importance of understanding humans as beings with the potential to comprehend, respect, and collaborate with individuals from diverse religious and cultural backgrounds. The concepts of intellect (akal) and fitrah (innate nature) in Islamic philosophy of education serve as the foundation for designing educational approaches that promote tolerance, interfaith dialogue, and social harmony in multicultural societies. The study also highlights the significance of education in facilitating a deeper understanding of the concept of humanity in Islam and how this understanding can serve as a basis for moderate behavior in a context of diversity. Practical implications of this research include the development of more inclusive and religiously moderate religious education curricula, as well as the promotion of sustainable interfaith and intercultural dialogue. Thus, this research contributes to a better understanding of how to address the challenges of religious moderation in multicultural societies using Islamic philosophy of education as a relevant and beneficial framework.